PERBANDINGAN STATUS GIZI MENURUT PENGUKURAN INDEKS MASSA TUBUH DAN PENGUKURAN PERSENTASE LEMAK TUBUH MENGGUNAKAN DXA SCAN DI RUMAH SAKIT X PEKANBARU - Rahel Lumban Toruan; Erwin Christianto; Huriatul Masdar (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2020)
Background Obesity can occur due to the accumulation of excess fat in the body.Obesity has been declared as a global epidemic by the World Health Organization (WHO). In 2016, more than 1,9 billions adults were overweight. In 2018, it was found that 24,1% of adults in Riau Province were obese with an incidence higher in women than men. Research Objectives This research is an analytical study to determine the comparison of nutritional status based on the data that has been collected from body mass index (BMI) measurement and body fat percentage measurement by DXA Scan, which was carried out on 364 adults aged 19-65 years. Metodology The data that has been obtained from BMI measurement will be grouped to four categories and the data that has been obtained from body fat percentage will be grouped to five categories based on their gender. The bivariate analysis using paired T Test will be done to see the p value. Conclusion From this study, it was found that most of the subjects were obese. According to the BMI examination, about 50,27% of the subjects were categorized as obese. Meanwhile, according to the body fat percentage measurement using DXA Scan, about 89,56% of subjects were included in the obese category. Based on the p value of 0,001 that obtained from the paired t test, it can be concluded that there are significant differences between these two methods. Keywords : BMI, DXA Scan, nutritional status, obese